THE EFFECTIVENESS OF THE APPLICATION OF CUSTOMARY LAW IN RESOLVING COMMUNAL LAND RIGHTS CONFLICTS - Maryana, Rina; Basir, Abd (JILPR Journal Indonesia Law and Policy Review, 2025)
Communal land rights (hak ulayat) refer to the hereditary ownership and management of land and natural resources by Indigenous communities. These rights are formally recognized and regulated in several national laws, including Law No. 5 of 1960 on Basic Agrarian Principles, Law No. 39 of 1999 on Human Rights, and Law No. 41 of 1999 on Forestry. Indigenous communities possess the authority to regulate, manage, and utilize land and natural resources within their territories in accordance with customary norms. This recognition aligns with Article 18B(2) of the 1945 Constitution, which affirms that the state acknowledges and respects Indigenous communities and their traditional rights as long as they remain viable and consistent with societal development and national principles. In practice, conflicts over communal land rights frequently arise among Indigenous groups due to overlapping claims, boundary disputes, and competing interests in natural resource use. This study employs an empirical research approach supported by field observations and interviews with Indigenous community members. The aim of the research is to analyze the underlying factors contributing to these conflicts and to identify effective mechanisms for resolving them, thereby reducing the potential for communal land rights disputes within Indigenous communities.